From Tradition to Modernity: Nina’s Quest for Hybrid Identity in Manju Kapur’s The Immigrant - SALAMI, Ali; PIRAYESH, Farnoosh (Anafora, 2023)
The paper explores the liberating power of Bhabha’s concept of hybridity in Manju Kapur’s novel The Immigrant. By concentrating on Nina’s immigration to Canada, the novel addresses her early affliction due to the cultural clash between the East and West, tradition and modernity, her assimilation problems, as well as her gradual assimilation, her in-betweenness, transformation in her roles and identity, and survival in the host world. She opens a space in-between the home and host culture, mediates between them, and becomes the citizen of two worlds; she thus enters the third space, i.e. she stands in-between two cultures prioritizing neither the home nor the host culture but the middle ground and emerges as a hybrid who occupies the in-between space and develops a double vision. Using Homi Bhabha’s insights, this study seeks to demonstrate that being positioned in the third space, i.e. moving beyond the polarities and challenging the fixedness of identity and experiencing in-betweenness – being neither one nor the other, might pave the way for her liberation. The paper is to show that Nina is neither one nor the other, i.e. neither a traditional nor a modern woman but both, simultaneously transcending and reconciling the tradition and modernity.